Dose-dependent effects of 2-acetylaminofluorene on hepatic foci development and cell proliferation in rats - Danai Tiwawech (2018)
Dose-dependent development of pre-neoplastk liver cell foci induced by 2-acetylaminofluorene (2-AAF) was investigated in relation to cell-proliferative activity. Male F344 rats were initially given a single i.p. injection of diethylnitrosamine (DEN, 200 mg/kg) and starting 2 weeks later received diets containing 2-AAF at dose levels of 150, 100, 60, 45, 35 or 30 p.p.m., 500 p.p.m. phenobarbital (PB) or basal diet as a control for 6 weeks. Two-thirds partial hepatectomy (PH) was performed at week 3. The rats were sequentially killed from weeks 0 to 16 and liver sections were analysed by double staining for both BrdU incorporation and glutathione S-transferase placental form (GST-P) expression. 2-AAF increased numbers and areas of GST-P positive (GST-P+) foci in a dose-dependent manner, especially after PH. Proliferation of hepatocytes, as indicated by BrdU labelling indices (LI), was higher in GST-P+foci than in surrounding hepatocytes in all 2-AAF-treated groups, even after cessation of carcinogen administration. Proliferative response of hepatocytes to PH was delayed in rats treated with the highest dose of 2-AAF in both foci and in surrounding areas possibly due to the 2-AAF toxicity. In the PB treated group, the results were similar to those for the lower dose 2-AAF-treated groups. It is concluded that the development of GST-P+foci and cell proliferation in GST-P+foci are directly related to 2-AAF treatment in a dose-dependent manner and the present assay system is reliable for detection of carcinogenicity of chemicals even at low doses. © 1991 Oxford University Press.